Response of the coffee berry borer (Hypothenemus hampei) to attractant traps in Robusta coffee plantations - RIMBING, JIMMY; ENGKA, REITY; DUMALANG, SHERLIJ; RORONG, FRANGKY (The Indian Journal of Agricultural Sciences, 2023)
Coffee berry borer (CBB), Hypothenemus hampei Ferrari , is a big challenge for farmers worldwide. The CBB life cycle may be found in coffee beans, making attractant traps an effective management method. Furthermore, during 2021 and 2022, the attractant traps were used to examine the effect on population density in Robusta coffee plantations. The treatment consisted of Cap Tikus ethanol (local), methanol, and a mixture of Cap Tikus ethanol-methanol. The results showed that all three traps could attract female beetles, and the highest CBB population caught was in 2021. A significant mixture towards the population was 68.15±60.42 CBB/trap/7 days and 35.75±8.39 CBB/trap/7 days in 2021 and 2022. The lowest fluctuation population of beetles caught was in Cap Tikus ethanol. The population was low at the first 7 days of observation, then increased at 21 and 28 days in 2021 (418–532 CBB/7 days) and 2022 (194–294 CBB/7 days). Furthermore, the high rainfall and rainy days negatively affect the caught beetles’ population. Based on the results, the attractant traps are a method to monitor and control CBB in coffee plants.